The Effects of the COVID-19 Pandemic on Prison Overcrowding in Jamaica - Leslie, Dacia L. (Victims & offenders, 2025)
In 2019, at the start of the COVID-19 pandemic, Tower Street Adult Correctional Centre, one of Jamaica’s two maximum-security centers for men, was operating at 94.5% above its ideal capacity of 850. The extent to which the Jamaican state took steps to facilitate decarceration during this period remains under investigated. This article provides a sketch of how the pandemic’s first phase influenced prison overcrowding in Jamaica, focusing on the crisis’s effects on prison populations and conditions. Using a mixed-methods approach, it is argued that while reduced intake and visitation suspension mitigated demographic overcrowding, prolonged lockdowns and restricted access to trials and rehabilitation interventions exacerbated social and operational overcrowding. The article ends with insights and recommendations for improving prison conditions and managing prison overcrowding, particularly in a pandemic context.